2021
DOI: 10.1002/oby.23147
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Adipose Tissue Immunity: Outrunning Inflammation

Abstract: Chronic inflammation is considered a precipitating factor and possibly an underlying cause of many noncommunicable diseases, including cardiovascular disease, metabolic diseases, and some cancers. Obesity, which manifests in more than 650 million people worldwide, is the most common chronic inflammatory condition, with visceral adiposity thought to be the major inflammatory hub that links obesity and chronic disease. Adipose tissue (AT) inflammation is triggered or heightened in large part by (1) accelerated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 111 publications
0
13
0
Order By: Relevance
“…Animal models demonstrated that as little as 4 weeks of aerobic exercise prevents conformational changes in adipose tissue [ 112 ]. In an early systematic review, physical activity with aerobic exercise inhibits adipose tissue paracrine and endocrine inflammatory responses [ 113 ]. This may result in children being less susceptible to infections.…”
Section: Impact Of Pediatric Obesity and Subsequent Adipose Tissue Dy...mentioning
confidence: 99%
See 1 more Smart Citation
“…Animal models demonstrated that as little as 4 weeks of aerobic exercise prevents conformational changes in adipose tissue [ 112 ]. In an early systematic review, physical activity with aerobic exercise inhibits adipose tissue paracrine and endocrine inflammatory responses [ 113 ]. This may result in children being less susceptible to infections.…”
Section: Impact Of Pediatric Obesity and Subsequent Adipose Tissue Dy...mentioning
confidence: 99%
“…Interestingly, leptin levels were increased in the obese pediatric populations [ 117 ] and seen in blood as early as 12 years of age [ 118 ]. In patients who had weight loss by physical activity including aerobic exercise, M1 macrophages along with inflammatory cytokines are decreased [ 113 ] proving how early interventions can diminish this inflammatory cascade.…”
Section: Blood Biomarkers As a Reflection Of Adipose Tissue Dysfuncti...mentioning
confidence: 99%
“…In general, inflammatory activation of various immune cells is associated with a marked shift toward glycolytic metabolism and lower reliance on fat oxidation. The increase in glycolysis triggers HIF1α-mediated gene transcription and cytokine production [50]. However, in a basal situation or in long-term regenerative processes after acute inflammatory responses, immune cells can use fat as an energy substrate.…”
Section: Immunometabolism: a Recent Conceptmentioning
confidence: 99%
“…Pharmacologically, agents targeting improvements in adipose tissue insulin sensitivity (e.g., thiazolidinediones) reduce circulating NEFA, liver fat, and hepatic fibro‐inflammatory activity 10 . Alternatively, exercise is a lifestyle therapy that may be able to improve adipose tissue insulin sensitivity through morphological and biochemical alterations within adipocytes 11–13 . Although studies have examined the impact of exercise on the sensitivity of adipose tissue to insulin, no attempt has previously been made to systematically aggregate data in this area, and it is unknown whether factors such as exercise mode, duration, intensity, and weight loss influence exercise training responses.…”
Section: Introductionmentioning
confidence: 99%